Studi Pengaruh Penambahan Tanah Lempung A-7 terhadap Kuat Geser Tanah Pasir Sungai - Putri Sumpeni Sagala (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Sand or the coarse grained soil is one type of soil that often causes problems in civil engineering working.Â The weakness of this soil is not having holding capacity each other. Sand is a kind of non-cohesive soil means has loose characteristic.Â This characteristic can be repaired by gradation suitable or mixed with the other type of soil that can make its shear strength increased. Clay soil A-7 is one type of soil that has smooth grain and cohesive characteristic. Clay soil A-7 is a plasticity soil that has high volume changed characteristic showed by its loose percentage on sieve no.200 is more than 35%. The clay soil A-7 added into this research was 0%, 15%, 20%, 25%, and 30%. The observation used direct shear by standard compaction proctor. The result showed that the addition of clay soil A-7 had significant effect on the river sand shear strength. The maximum cohesion score was obtained on 25% clay soil A-7 at 32,197 KPa, the maximum internal friction angle score was obtained on 15% clay soil A-7 at 38,15Â° and the maximum shear strength score was obtained on 15% clay soil A-7 at 156,295 KPa. Key Words : River sand, clay soil A-7, cohesion, internal friction angle, shear strength, direct shear